2022
DOI: 10.3390/applmech3030049
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Robots, Perception, and Tasks in Precision Agriculture

Abstract: This review reports the recent state of the art in the field of mobile robots applied to precision agriculture. After a brief introduction to precision agriculture, the review focuses on two main topics. First, it provides a broad overview of the most widely used technologies in agriculture related to crop, field, and soil monitoring. Second, the main robotic solutions, with a focus on land-based robots, and their salient features are described. Finally, a short case study about a robot developed by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 191 publications
0
25
0
1
Order By: Relevance
“…In addition, Yin et al ( 2021 ) stated that PA technology improves production by accounting for dynamics within sustainable agricultural systems and ISTAT-CREA ( 2022 ) estimated that the introduction of precision farming techniques will result in a reduction in pesticide use estimated at 25 to 40 percentage. However, in spite of several studies demonstrated the importance of PA technology application (Botta et al 2022 ; Bouma 2007 ; Carrer et al 2022 ; Colucci et al 2022 ), its adoption is still limited in Italy (Finco et al 2021 ). A number of studies reported a positive but slow trend (Smart Agrifood Observatory 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yin et al ( 2021 ) stated that PA technology improves production by accounting for dynamics within sustainable agricultural systems and ISTAT-CREA ( 2022 ) estimated that the introduction of precision farming techniques will result in a reduction in pesticide use estimated at 25 to 40 percentage. However, in spite of several studies demonstrated the importance of PA technology application (Botta et al 2022 ; Bouma 2007 ; Carrer et al 2022 ; Colucci et al 2022 ), its adoption is still limited in Italy (Finco et al 2021 ). A number of studies reported a positive but slow trend (Smart Agrifood Observatory 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tracks are known to outperform wheels in terms of improved traction on steep hard and soft surfaces, and better obstacle negotiation [1,2]. Tracked robots have been successfully demonstrated in many applications, including urban search and rescue [3], automation of industrial processes [4], explosive ordnance disposal [5], and precision agriculture [6]. Some innovative concepts have been proposed to further improve state-of-the-art mobility, for example, PackBot [7], Quince [8], and Mothership [9].…”
Section: Introductionmentioning
confidence: 99%
“…In agriculture, the use of AI is envisioned as “delivering real value” to farmers (Smith, 2018) and steering society toward the “fourth industrial revolution” or agriculture 4.0 (Lele & Goswami, 2017) via smart farming methods and decision‐making tools. Precision agriculture (PA) is one such “data‐driven strategy” to improve soil and resource management plans, and manage crops and livestock (Botta et al., 2022, p. 831). PA integrates information technology into farm machinery and farm management using innovations such as satellites, drones, sensors, and AI systems to help farmers make site‐specific and timely decisions (Rossel & Bouma, 2016; Klerkx & Rose, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PA integrates information technology into farm machinery and farm management using innovations such as satellites, drones, sensors, and AI systems to help farmers make site‐specific and timely decisions (Rossel & Bouma, 2016; Klerkx & Rose, 2020). Broadly, PA performs four major functions for farmers and their crop fields: independent navigation within the field, sensing field‐based changes, mapping and reporting of collected data, and making suggestions on management zones within the farm (Botta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%